Injuries and treatment in the oropharynx associated with sars-cov-2 - Li-Pereyra, Carmen Del Pilar (2022)
COVID-19 is a communicable disease caused by severe acute respiratory syndrome (SARS-COV-2). The oral cavity is a route of entry for SARS-COV-2. Oral epithelial cells, taste buds, and glands play an important role as they express cellular entry factors for SARS-COV-2, such as angiotensin-converting enzyme 2 (ACE2) and type 2 transmembrane serine protease (TMPRSS2).Oropharyngeal manifestations were found in the oral cavity, mainly in the tongue and hard palate. In mild cases, the use of alcohol-free mouthwash Chlorhexidine 0.12%, antibiotic therapy, and in severe cases photobiomodulation therapy was indicated, in other cases the lesions disappeared as the disease subsided.The virus can be detected in saliva, even before symptoms of COVID-19 appear. Reducing oral viral load could lead to a lower risk of transmission mainly through salivary droplets or aerosols. The use of mouthwashes is intended to reduce the bacterial load in infected patients who come to dental care. Among them we have chlorhexidine used in two concentrations of 0.12% and 0.2%. Both were found to be effective. Another of them is cetylpyridinium chloride, there is evidence that its use reduces viral load in patients with COVID-19 for up to six hours. Povidone iodine has also been shown to reduce viral load as a 0.23% mouthwash for 15 seconds prior to dental consultation. Another of the rinses used for this purpose is 1% hydrogen peroxide, since SARS-COV2 is vulnerable to oxidation.